Impact of COVID-19 on Stock Market Volatility and Forecast using ARIMA and EGARCH (Global Journal of Human-Social Science, 2023)
It is obvious that COVID-19 has caused unprecedented global economic crises The study forecast stock amidst the negative shock of COVID-19 and also examine the effect of novel COVID-19 on the stock exchange market by employing ARIMA and EGARCH model using daily data of Ghana Stock Exchange Composite Index from October 2017 to February 2021
Keywords: covid-19; stock exchange; composite index; autoregressive; moving average; ARIMA; GARCH